Effect of Feeding Berseem Fodder Grown Using Natural Farming Practices on Growth, Serum Metabolites, Interleukins and Semen Qualities in Barbari Goats - Kumar, Ravindra; Kumar, Arvind; Ravi Ranjan; Chand, Dinesh (Indian Journal of Animal Nutrition, 2026)
Berseem fodder (Trifolium alexandrinum) was cultivated using natural farming practices and evaluated in Barbari goats for their effect on growth, serum metabolites, interleukins and semen quality. Ten growing Barbari goats (Avg. BW 19.15± 0.87) age about 10 months were divided into two groups (CON and NAT) of five each as per completely randomized design. Animals of both the group were fed with Bengal gram Straw, concentrate pellet and green Berseem fodder. The goats of CON group was fed with green Berseem cultivated using conventional practices while goats of NAT group was fed with green Berseem cultivated using Natural farming practices The experiment was conducted for 120 days out of which 60 days was for growth study. Serum metabolites and semen quality was studied after 120 days of feeding. The average daily gain (ADG) was 90.33 g for Gr CON while 74.33 g for Gr NAT. Dry matter intake (g) was 766.71 and 759.16 for Gr CON and Gr NAT respectively. Among serum metabolites glucose, protein, albumin, triglycerides, urea was statistically similar among groups. Aspartate aminotransferase (AST) and cholesterol was lower in goats fed with naturally grown Berseem fodder. Immunity indicators like IL 1, IL6, TNF and total antioxidant was also similar among groups. No difference was reported on semen quality parameters like semen volume, mass motility, live percent and post thaw motility between groups. Present study concluded that feeding Berseem fodder grown using Natural farming practices had no significant effect on growth, metabolites and semen quality.